MEKANISME KOPING DAN ADAPTASI STRESS PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA DI RSUD WALED KABUPATEN CIREBON - Bambang Adi Purnomo; Yani Kamasturyani; Cecep Wahyudin (Jurnal Kesehatan Mahardika, 2020)
Chronic renal failure is a disease that results in a progressive and gradual decline in renal function that requires hemodialysis therapy. In Indonesia, there were 198,575 patients chronic kidney failure in 2018. The number of undergoing hemodialysis therapy is 132,142 patients. The hemodialysis routine causes tension, anxiety, stress and depression in patient. The purpose of this study was to determine the relationship between coping mechanisms and stress adaptation in chronic renal failure patients undergoing hemodialysis therapy ant Waled Hospital. The method of this research was descriptive correlational with a cross sectional approach. This research used purposive sampling technique amounted to 79 respondents. The instrument of this research was a questionnaire Jaloweic Coping Scale (JCS) and stress adaptation questionnaire. Data analysis used the spearman rank test. Place of research at Waled Hospital, Cirebon Regency during July 2020.  The result showed that most respondents had an adaptive category as many as 55 adaptation showed the results of most respondents had an adaptive category as many as 55 respondents with a percentage (69.6%). The spearman rank test showed p value <α and r<1, which means that there was a moderate an positive relationship between coping mechanisms and stress adaptation (p value=0,000 < α=0.05 and r=0.593). The is a relationship between coping mechanisms and stress adaptation in chronic renal failure patients undergoing hemodialysis therapy. The better coping mechanism is carries out, the adaptive stress that arises will be adaptive so that the patient can adjust and be able to cope with the stress he is experiencing.